Cognitive Framework Underlying Learning Strategies for Academic Speaking - Irawati, Lulus (English Teaching Journal, 2013)
This article aims to discuss about cognitive framework underlying learning strategies for acadeic speaking. Cognitive framework underlies learning strategies, since there are four stages of encoding process that cover not only the way store things to be learnt but also the way people organize way store things to be learnt but also the way people organize. Moreover, the learning strategies are helpful for motivating the students to be active and creative in order to develop their communicative competence. In the learning strategies, the students are encouraged to participate actively in real communication. Hopefully, this article can give contribution to the teacher and lecturer in teaching speaking skill